Euphoria. Complete seasons 1+2 [videorecording (DVD)]. - Zendaya, 1996-; Schafer, Hunter; Cloud, Angus; Dane, Eric, 1972-; Ferreira, Barbie, 1996-; Apatow, Maude; Elordi, Jacob, 1997-; Demie, Alexa, 1994- (Home Box Office, Inc., 2022)
Season 1 of this intense HBO drama focuses on 17-year-old Rue Bennett (multimedia star Zendaya), a drug addict fresh from rehab who's struggling to stay clean. Ahead of the second season, the Emmy-winning series returns with two special episodes set over the Christmas holiday. Season 2 continues to follow Rue's dynamic group of friends as they enter a new year and question their choices.